Intercultural Communication Dynamics (A Case Study of Conflicts Among East Nusa Tenggara Students at Tambak Bayan) - Desy Rahma Wati; Fathimatuz Zahroh (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
ulture is considered as an inseparable heritage from humans so that many people tend to assume it is inherited genetically. The many cultures often cause several problems. One of them is that people think that Eastern students are a little different. Only a few individuals create a negative stigma that is strongly attached to Eastern students. The purpose of this study was to see how the dynamics of conflict and adjustment of NTT students in Tambakbayan Yogyakarta. To maintain a good relationship between NTT students and Tambakbayan residents. This study is a qualitative descriptive study, data collection was carried out by interviewing and collecting data from the media. The data validity test is technical triangulation and source triangulation and is analyzed continuously by reducing data, displaying data, verifying data. The results of this study indicate that differences in language, habits, and perceptions make it difficult for NTT students to communicate in Yogyakarta. In addition, the existence of stereotypes attached to NTT students such as being backward, like making trouble, and being prone to committing crimes is a source of gaps between NTT students and students from other regions. ultimately fostering ethnocentric attitudes in each group. It would be better if NTT students and Tambakbayan residents collaborate so that inter-ethnic relations can improve and a sense of comfort can be achieved.